A Different Look at the Past — a Tour with Objects at the Archaeological Open-Air Museum Oerlinghausen - Sylvia Crumbach (EXARC, 2016)
Due to the inclusion program at schools in North Rhine Westphalia, the need arose to organise guided tours through the museum in such a way that visually impaired participants could be included in the experience. The idea was to offer an additional level of experiencing information through touch, by creating individual purpose-made objects in combination with narratives depending on the educational objectives as a key term for a humane society that respects diversity. The measure is funded by the Westphalian Museum Office.